Flexible microsupercapacitors using silk and cotton substrates - Das, Chayanika; Krishnamoorthy, Kothandam (ACS Applied Materials & Interfaces, 2016)
Flexible microsupercapacitors (MSCs) are needed to power ultrasmall wearable electronic devices. Silk cocoons comprise microfibers of silk, which is an attractive natural resource to fabricate MSCs. These fibers are insulators; hence, they must be converted to conducting surfaces. Polyphenols from green tea have been used as a protective layer that also acted as a reducing agent for silver ions. The reduction of silver ions resulted in the formation of silver nanoparticles that subsequently reduced gold ions to gold. The gold film imparts conductivity to the silk fiber without affecting the mechanical strength of the silk fiber. The mechanical strength of uncoated silk fiber and gold coated silk fiber were found to be 5.2 and 5 GPa, respectively. A pseudocapacitive polymer, poly(3,4-ethylenedioxythiophene), was used as the active material to fabricate MSCs. The MSCs showed an impressive gravimetric capacitance of 500 F/g and areal capacitance of 62 mF/cm(2). The power and energy densities were calculated to be 2458 W/kg and 44 Wh/kg, respectively. The device was coiled on a cylinder, and the performance of the device was found to be same as that of the uncoiled device. To demonstrate that the approach is not specific to silk, we also coated gold on cotton fibers using the protocol used to coat gold on silk. Coiled and uncoiled supercapacitors were fabricated using PEDOT coated cotton fibers. The gravimetric capacitance was found to be 250 F/g with energy and power densities of 5.5 Wh/kg and 1118 W/kg, respectively. We have also demonstrated that the devices can be connected in parallel and series to improve the performance of the miniaturized devices.

Fabrication, characterization and comparison of DSSC using anatase TiO 2 synthesized by various methods - Umale, Sanjivani V.; Tambat, Sneha N.; Vediappan, Sudhakar; Sontakke, Sharad M.; Krishnamoorthy, Kothandam (Advanced Powder Technology, 2017)
In this study, anatase TiO2 nanoparticles were synthesized by three techniques, namely, sol-gel, acid-base co-catalyst and room temperature colloidal methods. The synthesized materials were characterized by X-ray diffraction, scanning electron microscopy, pore diameter, pore volume and surface area. The dye-sensitized solar cells were fabricated using the synthesized materials and characterized for incident photon to current conversion efficiency, photocurrent density to photo voltage measurement and electrochemical impedance analysis. Among the studied materials, TiO2 synthesized by sol-gel method displayed highest photon to current conversion of 76.8% and a maximum solar cell efficiency of 7.85% with Jsc of 14.75mA/cm², Voc of 0.76V and FF of 0.7. This is the first study to report a high power conversion efficiency of DSSC using a sol-gel synthesized titania and its comparison with other two synthesized materials. The high power conversion efficiency of the solar cell using TiO2 synthesized by sol-gel method is attributed to its characteristic properties such high surface area, larger pore diameter and larger pore volume and highest dye loading capacity.

Far-red active unsymmetrical squaraine dyes containing N-arylated indoline donors for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Jayaraj, Nithyanandhan (Photochemistry and Photobiology, 2024)
Squaraine dyes possess sharp far-red active transition with high extinction coefficient and form aggregates on TiO2 surface. Aggregation of dyes on TiO2 has been considered as a detrimental factor for DSSC device performance, which can be controlled by appending alkyl groups to the dye structures. Hence by integrating alkylated (alkyl groups with both in-plane and out-of-plane) aryl group with indoline moiety to make it compatible with other electrolytes and for controlling the dye-aggregation, a series of squaraine acceptor-based dyes SQA4-6 have been designed and synthesized. SQA4-6 dyes showed absorption between 642 and 653 nm (lambda max), photophysical and electrochemical studies indicated that the HOMO energy levels of this sets of dyes are well aligned with the potentials of I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$ and [Co(bpy)3]2+/3+ redox shuttles for better dye regeneration process. DSSC device efficiency of 3% has been achieved for SQA5 dye with iodolyte (I-/I3-\$\$ {\textbackslashmathrm{I}}_3<\^>{-} \$\$) electrolyte in the presence of 0.3 mM of chenodeoxycholic acid (CDCA). The IPCE profile of DSSC device fabricated with SQA4-6 dyes indicated the contribution of aggregated structures for the photocurrent generation. Dye-sensitized solar cell (DSSC) device efficiency of 3% (Jsc 5.72 mA cm-2, Voc 662 mV and ff 79%) has been achieved for an unsymmetrical squaraine dye, SQA5 with iodolyte electrolyte and the incident photon to current efficiency (IPCE) profile indicates the contribution of aggregated structures for the photocurrent generation.*image
Keywords: aggregation of dye; arylation on N-atom of indoline donor; dye-sensitized solar cell; squaraine dye

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye